DISSEMINATING TEXTILE SLUDGE INDUCED HEAVY METAL CONTAMINATION AND ASSOCIATED HEALTH RISKS IN CONTEXT OF DHAKA, BANGLADESH (American International Journal of Nursing Education and Practice, 2021)
This study investigates the present scenario of heavy metal contamination in textile sludge along with their associated health problems, their removal efficiencies, alternative usage, and challenges to handling them in the perspective of Bangladesh. Textile sludge is considered to be the biggest source of hazardous elements and has the potential characteristics to create different diseases in human beings including cancer. Since the sludge is associated with a high load of heavy metals, it poses threat to both environment and human health if they remain untreated in an open environment. The methodology of this study focuses on a systematic review of data related to sludge-induced heavy metal contamination around Dhaka city. Results showed that Cr, Ni, Cu, As, Pb, and Cd were found to be dominant elements in the sludge that may pose serious threats to human health. This study also pointed out some treatment methods to remove heavy metals from textile sludge load, but however, still, there is a long way to implement them on a large scale with reduced economic, health, and environmental costs. This study concludes that further analysis is needed to remove heavy metals and encourages the emerging application of textile sludge for sustainable development in the health economic sector of the country.JEL Classification Codes: L67, L61, P36, D81.